Tactical lexical knowledge of soccer by age 15 and 18 - Acoumambo, D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction According to the theory of the development of lexical knowledge (Lieury & Lorant, 2013), the lexicon is built progressively over the course of life through different stages and experiences. The objective of this study is to measure the effect of age on the size of the football tactical lexicon.